Panama : Locking in Success - Koehler-Geib, Friederike (World Bank, Washington, DC, 2015)
Panama has made significant progress in reducing poverty in recent years, progress that compares positively to that of the rest of the Latin America and Caribbean region. This report takes stock of this progress and reflects on the constraints and opportunities that Panama faces in continuing on its path of shared prosperity and poverty reduction. The education and skills agenda, energy, public sector reform, the inclusion of indigenous peoples, and water management are identified as areas that will require attention to ensure the sustainability of Panama’s success story. Following a detailed analysis of poverty—recent trends, drivers of poverty reduction, and demographic factors—the report provides foundations to answer three main questions: • What has driven growth in Panama in recent years? • To what extent has this growth been, or not been, inclusive? • How sustainable is the growth and more generally, the development model of Panama?